Refuge use by prey dependent on the number of predators in a Gause-type model - Gallar, Virginia Belén (2025)
This paper deals with a continuous-time predator-prey model of Gause-type considering the use of a physical refuge by a fraction of the prey population. The fraction of hidden prey is assumed to be dependent on the presence of predators in the environment. The conditions for the existence of equilibrium points and their local stability are established. According to these results, the extinction of both species is not possible, and they coexist over the long term. We conclude that the dynamics of the studied model are very similar to the model that does not consider prey refuge. However, this cannot be stated if another function is used to describe this anti-predator behavior.